Substitution of the significance of the choice of a design solution and its impact on the total cost of the life cycle of a construction object - TYTOK, Viktoriya; SYVOLAP, Yuliia (Ways to Improve Construction Efficiency, 2025)
The article examines in detail the process of optimizing production solutions related to the arrangement of floor coverings from various materials, including plank flooring, parquet floors, floors made of wooden panels and wooden boards. Particular attention is paid to the economic analysis of the choice of constructive and technological solutions in order to minimize costs and increase the efficiency of using available resources. To determine the optimal option for performing the work, the linear programming method was used, which allows taking into account numerous variables and restrictions. As part of the study, an objective function was formulated that reflects the maximization of profit from the performance of construction work. In addition, a system of constraints was developed that takes into account the available labor, material and technical resources, as well as the project implementation timeframe. Calculations were carried out using the simplex method, which made it possible to determine the optimal resource allocation plan and minimize costs at each stage of construction work. According to the results of the study, the best solution is to use chipboard for arranging floor coverings. This option has the highest desirability index, which indicates its superiority over other materials. Chipboard is also a competitive option. Board coverings and fiberboard bases, in turn, have lower desirability indices due to high costs and rapid wear. The results obtained can be used in construction design practice to make economically sound decisions that will contribute to increasing the total life cycle cost of construction projects. This will allow construction companies not only to reduce costs, but also to increase competitiveness in the market, offering customers more effective and cost-effective solutions.